The strategy in increasing creative economy during the COVID-19 pandemic - Yuliana, Yuliana (Goodwood Publishing, 2020)
Purpose: This paper aimed to comprehend the strategy to increase the creative economy during the pandemic, especially about e-commerce and supply chain. Research methodology: This is a review of the literature. This paper used the database in Science Direct and Google Scholar. The keywords used were COVID-19, creative economy, e-commerce, increase, supply chain, and strategy. Results: The effectiveness of the supply chain can be improved by analyzing the strengths, weaknesses, opportunities, and challenges (SWOT) so that strengths and opportunities can be optimized. E-commerce can be increased by enhancing creativity and innovation. Another way is cooperating with the government and other entrepreneurs. Limitations: This paper is a narrative literature review. There are only a few studies about e-commerce and the supply chain during the COVID-19 pandemic in this paper. Further studies are needed to increase the e-commerce and supply chain for each item and commodities during the COVID-19 pandemic. Contribution: The contribution of this paper is for the creative economy in increasing the effectiveness of supply chains and e-commerce.